Demand Analysis of the Whitefish Market in the EU - Has Pangasius Taken Over Market Shares in the Whitefish Market? - Hellandsjø, Lena Victoria (UiT Norges arktiske universitet, 2015)
The market for seafood has changed significantly during the last couple of decades. This is mainly due to two prevailing trends, that is the stagnation in harvest of wild fish and increased production of aquaculture species. The growth in the supply of aquaculture products is caused by both new species entering the market and an increased production of already established species. Given the vast changes in the global seafood markets, the Linearized Almost Ideal Demand System (LA/AIDS) is applied in order to investigate the impact pangasius as a new species has had on the demand for imported whitefish species (cod, Alaska pollock, and saithe) to the European Union. By looking at the development in market shares from 1988 to 2014, pangasius has seemingly taken over parts in the whitefish market. However, the estimation results from the LA/AIDS illustrate another story: While the increasing supply of pangasius imports has not had a significant effect on the demand of the other whitefish species in question, the elasticities differs for the periods before and after the increased supply. The degree of the substitution effects varies across species, though the expenditure elasticities are all close to one and positive apart from that of saithe.